Impact of Socioeconomic Status and Parental Involvement in Students’ Academic Performance of the Undergraduate Students in a Comprehensive University during the COVID-19 Pandemic - Lorenzo Roen Rumbaoa; Gabriel Vone San Jose; Joshua Andrei Sanchez; Ronaldo Cabauatan (UJoST- Universal Journal of Science and Technology, 2022)
Academic performance has been linked to parental involvement and socioeconomic status. In today’s era, education is not a privilege but rather a right for every population around the world. This study examined the relationship between socioeconomic status and parental involvement in the academic performance of undergraduate college students. This research aims to answer the central question, does Socioeconomic status and Parental Involvement affect Student Academic Achievement? The importance of addressing this question is that economic and educational institutions may use the findings of this research as a guide for future economic and educational development. Some previous research has shown that socioeconomic status had little to no effect on student academic achievement, while parental involvement affected student academic achievement. This study used stratified random sampling wherein 14 out of 17 colleges in the comprehensive university participated. This study used an online survey with questions pertaining to monthly household income, a 16-item 4-point Likert scale pertaining to parental involvement, and the latest estimated general weighted average. Results show that socioeconomic status has no significant relationship with student academic performance, while parental involvement has a significant relationship with student academic performance. Parental involvement must also be given focus on student academic performance. Which furthermore indicates that various household income would affect students’ academic performance.